The impact of Smart Money Kit on children’s financial knowledge, attitude and behavior / Mohamad Fazli Sabri ... [et al] - Sabri, Mohamad Fazli; Wijekoon, Rusitha; Ramli, Nurhayatul Nira; Moga Dass, Thinagaran (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Financial management is one of the vital requirements throughout everyday life, as one develops, the utilization of financial management recurrence would be extraordinarily expanded. Since, financial thinking could be developed, expanding the propensity for financial management and understanding financial-related awareness at a early age greatly affect encouraging future financial behavior. Hence, in this research the research group incorporated gamification and edutainment in to a tool called Smart Money Kit. The objective behind the inovation of Smart Money Kit is as an alternative financial education tool for parents, teachers and other adults to assist in educating children in personal financial management. The results demonstrated that the Smart Money Kit to be helpful regarding the enhancement of financial knowledge by 59%, positive financial attitudes by 21.9%, and better financial behaviour by 19.3% of the children. Therefore, the majority of the parents, teachers and caretakers agree that Smart Money Kit has guided their children to become financially prudent and 90% of them evidenced a huge difference in their children after being exposed to Smart Money Kit. Hence this kit has been proved to be an effective tool to educate children on financial literacy besides able to develop a positive financial attitudes and better financial behaviour among the children.